2002
DOI: 10.1159/000048423
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias: Incidence and Effects on Psychosexual Development as Evaluated with the Minnesota Multiphasic Personality Inventory Test in a Sample of 11,649 Young Italian Men

Abstract: Purpose: We evaluated the incidence of hypospadias and its effects on psychosexual development in a sample of 11,649 young Italian males. Over the last 30 years only about 30 major publications have addressed these issues and the results of many studies have been contrasting. Some defects in methodology, such as low response rates, heterogeneity of age ranges and the choice of controls, have been the main limitations. Our study was designed to take these problems into account. Materials and Methods: Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 9 publications
3
54
1
3
Order By: Relevance
“…Mondaini's group [29] performed a cross-sectional study in 500 men including 42 men with a history of hypospadias, and were thereby unable to provide a follow-up rate. The remaining 19 cohort studies reported a mean response rate of 48.4% (21.7e100%; 1027/ 2120 patients).…”
Section: Generalmentioning
confidence: 99%
“…Mondaini's group [29] performed a cross-sectional study in 500 men including 42 men with a history of hypospadias, and were thereby unable to provide a follow-up rate. The remaining 19 cohort studies reported a mean response rate of 48.4% (21.7e100%; 1027/ 2120 patients).…”
Section: Generalmentioning
confidence: 99%
“…These factors may become more important if a child has repeated operations due to two stage repairs or after complications (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover previous studies demonstrated that andrological disorders were found in about 30% of youngsters: these data have been confirmed by the mean rate of 31.7% found in the present series independently from the geographical area investigated.The logical explanation of this phenomenon could be that a lot of students are adequately informed on medical glossaries but not on their body health awareness to avoid subsequent complications on fertility and couples's sexual problems. Hypospadia and disorders of sex development such as pseudo-hermaphroditism, have always already been diagnosed in all cases found in both military and school check-ups while less evident diseases such as penile congenital curvature and short prepucial fraenulum have been diagnosed just after a projection of slides session (11). About 1% of subjects showed a substantial reduction of testicular volume and all of them were counselled to check a second level visit to test the presence of complicated diseases such as Klinefelter Syndrome (KS) (karyotipe 47, XXY).…”
Section: Discussionmentioning
confidence: 99%